Restoration of the morphological and functional properties of erythrocytes in donated blood after hypothermic storage - Gulevsky, A. K.; Zharkova, E. E. (Reports of the National Academy of Sciences of Ukraine, 2016)
The restorative effect of a low molecular weight fraction of cord blood on erythrocytes in donated blood of man on such indicators as the morphology and the oxygen-transport function is investigated. The perspective of using the rehabilitative environments based on cord blood is shown.